Tengkolok as The Heritage of Perak Darul Ridzuan: The Binder, Techniques, Manner & Amp; Taboo - Manan, Salina Abdul; Haron, Hamdzun; Ramli, Zuliskandar; lsmail, Noor Hafiza (2015)
Tengkolok is a unique head covering for Malay men and it is still worn to this very day.However, its adornment only is limited to certain functions and events. With this, this artideis written to document in further detail the binders of the Malay-inherited tengkolok especiallyin the state of Perak DaruiRidzuan. Some questions need to be answered, such as 'who arethe tengkolok binders in Perak?', 'how are the tengkolok-folding techniques used?' and 'whatare the etiquettes and taboo in the making of tengkolok?'. Offering explanation, aqualitative culbJral approach will be adopted. Both interview and observation will be used toobtain data wither in writing or visually. The observation done has suggested that there arefour tengkolok binders who are still active in Perak. Each of them has their own respectivetengkolok folding techniques. This artide will discuss the work of these binders, their foldingtechniques, the manner and etiquettes as well as the taboo in tengkolok-making. It isanticipated that this article would be able to catch the interest of researchers especiallylhose studying Malay textiles and clothing also the younger generation in order for themknow tengkolok better and at the same time to learn this skill. Our observation is also ofhigh value as it is able to contribute to the sustainability of tengkolok-binding heritage thathas long been of 'low-profile and not really popularised among the younger peoplenowadays. The documentation of this tangkolok binder would serve as one of the ways toappreciate tengkolok-binders as part of the Malay priceless heritage Universitas Riau Universitas Malaysia